Efektivitas Pelayanan Kesehatan di Daerah Terpencil Indonesia melalui Telemedisin: Review Literatur Sistematis - Miftah Hayati (Awatara Publisher, 2025)
The development of digital health has encouraged the implementation of telemedicine as a solution to improve healthcare access in Indonesia. Supported by regulations such as Law No. 17 of 2023, Government Regulation No. 28 of 2024, and Minister of Health Regulation No. 20 of 2019, telemedicine plays a crucial role in enhancing technology-based healthcare services. This study aims to evaluate the effectiveness of telemedicine policies in improving healthcare access and service quality, as well as to identify key challenges related to regulations, infrastructure, and patient data protection. A systematic literature review (SLR) was conducted using fifteen primary references focusing on digital health regulations, telemedicine service implementation, and patient data security in Indonesia. The findings indicate that telemedicine has successfully expanded healthcare access, yet continues to face barriers in regulatory standardization, infrastructure readiness, and data protection. It is concluded that telemedicine policies should be strengthened through clearer regulations, improved digital infrastructure, and integration of health technology services to ensure equitable and high-quality healthcare for the Indonesian population.